Care-full commoning at the Old Church on the Hill, Bendigo. Issue 4 (2nd October 2019) - Parris, Daniel; Williams, Miriam
ABSTRACT: Increasingly, the notion of the commons has been mobilised as a way to articulate the possibility of other ways of doing/being/thinking life which are at odds with the logics of enclosure. Whilst practices of care have been identified as central in sustaining commons, there remains a need for more detailed conceptualisations of how commons are maintained through everyday practices of care. In this paper we draw on research conducted at The Old Church on the Hill in Bendigo, Victoria, Australia, to provide an account of the role, complexities and constraints of care in constituting a commons. Throughout the paper we develop the concept of care-full commoning which encapsulates the phases of care identified by Tronto (1993. Moral Boundaries, A Political Argument for an Ethic of Care . New York and London: Routledge, 2013. Caring Democracy: Markets, Equality, and Justice . New York: NYU Press) and is a term we use to describe the multiple ways that care is practiced through, in, and by human and non-human others that comprise commoning collectives. We discuss the everyday practices of care that have sustained this commons over time, arguing that paying attention to the work of care in maintaining commons is an important political task.